Landasan fikih dalam perancangan arsitektur: Perspektif Al-quran dan Hadis - munir, akhmad (Maliki Interdisciplinary Journal, 2025)
This article discusses the foundation of Islamic jurisprudence (Fikih) in architectural design, focusing on the perspective of the Quran and Hadith. Fikih in architecture, as a discipline that integrates the principles of Islamic Sharia into building design, is crucial to ensure that every aspect of design not only meets functional needs but also aligns with the spiritual and social values taught in Islam. Through this approach, the study explores how Fikih law can be applied in the context of architecture, and how values such as simplicity, justice, and respect for the rights of others can be integrated into building design. Furthermore, this article highlights the relevance of applying architectural jurisprudence to address modern challenges, such as the need for environmental sustainability, spatial efficiency, and technological developments in the construction sector. Thus, this study not only offers theoretical understanding but also makes a practical contribution to creating Islamic architecture that adapts to current developments without neglecting sharia principles.